An Analysis of Influence of Network Topology on Power Network Reliability Based on OPLC. Issue 1 (1st October 2022) - Fu, Lina
Abstract : Optical fiber to the home (PFTTH) is an access network technology, which uses optical fiber composite low voltage cable (OPLC) to realize the deep integration of the power grid and communication network infrastructure. Key technologies include network structure design and high-speed access technology, PON technology, and the OPLC technology. This paper introduces the key technologies of power fiber-to-home networking and the influence of network topology on the reliability of PFTTH.